Emotional Testimonies: An Ethnographic Study of Emotional Suffering Related to Migration from Mexico to Arizona - Crocker, Rebecca (Frontiers in Public Health, 2015)
It is increasingly argued that social and economic inequities poorly affect overall health. One of the means through which these inequities are translated to the body is via negative emotions, which carry known psychological and physiological responses. This paper examines migration-related psychosocial stressors impacting first-generation Mexican immigrants in southern Arizona, and reports on the primary emotional experiences immigrants associate with these stressors. Data were drawn from a qualitative, ethnographic study conducted over the course of 14 months during 2013–2014 with first-generation Mexican immigrants (N = 40) residing in Tucson Arizona and service providers working directly in the immigrant community (N = 32). Results indicate that the primary structural vulnerabilities that cause emotional hardship among immigrants are pre-migration stressors and adversity, dangerous border crossings, detention and deportation, undocumented citizenship status, family separation, and extreme poverty. Many of these factors have intensified over the past decade due to increased border security and state level anti-immigrant legislation in Arizona. Immigrants connected these hardships to the emotions of trauma (50%), fear (65%), depression (75%), loneliness (75%), sadness (80%), and stress (85%), and most respondents reported suffering from three or more of these emotions. Given the heavy emotional toll of migration and the direct impact that regional legislation and border security had on well-being, this paper argues that emotion be considered an important mechanism for health declines in the immigrant community. In order to stem the frequency and intensity of emotional stress in the Mexican immigrant community in Tucson, it is imperative to support organizations and policies that promote community building and support networks and also expand access to and availability of mental health services for immigrants regardless of documentation status.